Competition on banking - a new outlook - Bissember, Enid (Central Bank of Barbados BridgetownBB, 1992)
Considers services offered by commercial banks in an underdeveloped economy, focussing on the effects of Central Bank control on their services. Also looks at the effect of greater competition on the banking industry.